PEMANFAATAN ECOBRICK SEBAGAI BARRIER KEBISINGAN AKIBAT ARUS LALU LINTAS DI SDK YOS SUDARSO MAUMERE - Soludale, Anastasia Merdekawati Noralita; Yuneta, Margaretha; Pau, Dedi Imanuel (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
This research is motivated by the high noise level caused by traffic on Kesehatan street, which is located right in front of SDK Yos Sudarso Maumere. This can risk disrupting the learning process and the concentration of students and teachers at the school. The purpose of this study to analyze the effectiveness of ecobricks as noise barriers and the impact of using ecobricks as barriers on the quality of the school environment. This study uses a quantitative experimental approach, by measuring noise levels before and after the installation of ecobrick barriers. Measurements were carried out using a sound level meter placed in several classroom that were most affected by the noise. The results showed that before the installation of ecobrick barrier, the noise level (Leq) exceeded the noise quality standard threshold for educational areas (55 dB), which ranged between 60-65 dBA. The measurements results after the installation of the barrier show a decrease in noise levels ranging from 10-12 dB, bringing most of the noise levels below the required noise limit. The research results state that ecobricks are effective in reducing noise caused by traffic flow. The use of ecobricks also provides ecological benefits by reducing noise in school environments and managing plastic waste.